Variables Associated With Tic Exacerbation in Children With Chronic Tic Disorders. (March 2014) - Himle, Michael B.; Capriotti, Matthew R.; Hayes, Loran P.; Ramanujam, Krishnapriya; Scahill, Lawrence; Sukhodolsky, Denis G.; Wilhelm, Sabine; Deckersbach, Thilo; Peterson, Alan L.; Specht, Matt W.; Walkup, John T.; Chang, Susanna; et al.
Research has shown that motor and vocal tics fluctuate in frequency, intensity, and form in response to environmental and contextual cues. Behavioral models have proposed that some of the variation in tics may reflect context-dependent interactive learning processes such that once tics are performed, they are influenced by environmental contingencies. The current study describes the results of a function-based assessment of tics (FBAT) from a recently completed study comparing Comprehensive Behavioral Intervention for Tics (CBIT) with supportive psychotherapy. The current study describes the frequency with which antecedent and consequence variables were reported to exacerbate tics and the relationships between these functional variables and sample baseline characteristics, comorbidities, and measures of tic severity. Results showed that tic-exacerbating antecedents and consequences were nearly ubiquitous in a sample of children with chronic tic disorder. In addition, functional variables were related to baseline measures of comorbid internalizing symptoms and specific measures of tic severity.